PENGARUH HARGA, LABELISASI HALAL, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ROTI KACANG HJ. ELIYA LUBIS DI KOTA TEBING TINGGI - Nasution, Anriza Witi; Auliah, Dina; Wathan, Hubbul (Politeknik Negeri Medan, 2024)
This study was conducted to determine the effect of price, halal labeling and product quality on purchasing decisions. This study uses independent variables, namely price, halal labeling and product quality and dependent variables, namely purchasing decisions. Primary data used in the study were obtained from questionnaires that had been distributed to consumers of Roti Kacang Hj Eliya Lubis with a sample size of 101 respondents. This study uses a quantitative method using a Likert scale. Data analysis techniques use multiple linear regression, partial test (t test), simultaneous test (F test), determination test (R2) and autocorrelation test with a significance level of 5% (α = 0.05) which are processed using SPSS 25. The results of the partial test that has been carried out indicate that the variables price, halal labeling and quality partially have a significant effect on purchasing decisions. The variables price, halal labeling and product quality simultaneously have a significant effect on purchasing decisions